Redevelopment - Smith, George O. (George Oliver), 1911-1981; Williams, A. (Arthur) (Salt Lake City, UT : Project Gutenberg, 2022)
"Redevelopment" by Wesley Long is a science fiction novel written in the mid-20th century. The book explores themes of space exploration and human resilience, focusing on the challenge of interstellar travel and the interaction between human characters and extraterrestrial civilizations. The story follows protagonist John McBride, who is enlisted by Sandra Drake, a determined pilot, to assist in retrofitting her spaceship, the "Lady Luck", with a super-speed drive so she can search for her missing friend, Steve Hammond. As Sandra embarks on her journey to the Sirius system in search of Steve, the narrative shifts between her adventure and the ensuing challenges faced by McBride and Hammond, who take off in the "Haywire Queen" to follow her. The characters encounter various obstacles, including malfunctioning technology and the complexities of navigating new alien environments, while grappling with their feelings towards each other and the consequences of their daring endeavors. Ultimately, the quest highlights the human spirit's capacity to explore the unknown, seek connection, and navigate challenges, culminating in a mix of tension, adventure, and personal growth. (This is an automatically generated summary.)
Release date is 2022-06-16
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net.
Keywords: Science fiction; Space ships -- Fiction; Human-alien encounters -- Fiction; Interstellar travel -- Fiction